Transcriptional reprogramming underpins enhanced plant growth promotion by the biocontrol fungus Trichoderma hamatum GD12 during antagonistic interactions with Sclerotinia sclerotiorum in soil - Shaw, Sophie (Mol Plant Pathol, 2016)
The free‐living soil fungus Trichoderma hamatum strain GD12 is notable amongst Trichoderma strains in both controlling plant diseases and stimulating plant growth, a property enhanced during its antagonistic interactions with pathogens in soil. These attributes, alongside its markedly expanded genome and proteome compared with other biocontrol and plant growth‐promoting Trichoderma strains, imply a rich potential for sustainable alternatives to synthetic pesticides and fertilizers for the control of plant disease and for increasing yields. The purpose of this study was to investigate the transcriptional responses of GD12 underpinning its biocontrol and plant growth promotion capabilities during antagonistic interactions with the pathogen Sclerotinia sclerotiorum in soil. Using an extensive mRNA‐seq study capturing different time points during the pathogen–antagonist interaction in soil, we show that dynamic and biphasic signatures in the GD12 transcriptome underpin its biocontrol and plant (lettuce) growth‐promoting activities. Functional predictions of differentially expressed genes demonstrate the enrichment of transcripts encoding proteins involved in transportation and oxidation–reduction reactions during both processes and an over‐representation of siderophores. We identify a biphasic response during biocontrol characterized by a significant induction of transcripts encoding small‐secreted cysteine‐rich proteins, secondary metabolite‐producing gene clusters and genes unique to GD12. These data support the hypothesis that Sclerotinia biocontrol is mediated by the synthesis and secretion of antifungal compounds and that GD12's unique reservoir of uncharacterized genes is actively recruited during the effective biological control of a plurivorous plant pathogen.